An asymmetry in the acquisition of relative clauses: Evidence from Tagalog. Issue 6 (December 2019) - Tanaka, Nozomi; O'Grady, William; Deen, Kamil; Bondoc, Ivan Paul
This article reports on the acquisition of relative clauses in Tagalog, the most widely spoken language in the Philippines. A distinctive feature of Tagalog is a unique system of voice that creates competing patterns, each with different possibilities for relativization. This study of children's performance on agent and patient relative clauses in a comprehension task revealed an agent relative clause advantage. These findings cannot be explained by the voice preference in declarative clauses, but are compatible with an explanation based upon input frequency factors.